2022
DOI: 10.5055/jom.2022.0736
|View full text |Cite
|
Sign up to set email alerts
|

Patient engagement and prescription opioid use in perioperative pain management

Abstract: Objective: To examine (1) patient perceptions regarding their engagement and the engagement of their families in perioperative pain management, (2) demographic and clinical characteristics associated with perceived patient and family engagement, and (3) the association between perceived patient and family engagement and patient outcomes.Design: A prospective, observational study. Setting: The Personalized Pain Program (PPP) at the Johns Hopkins Hospital in Baltimore, Maryland.Participants: Patients having more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A total of 20% of respondents were African American, 73% were unemployed or disabled, and 54% were married. In comparison, 37% of the PPP population are African American, 60% are unemployed or disabled, and 36% are married [35]. While approximately 25% of the clinic's total population had seen the clinic psychiatrist, most respondents in this study (54%) received psychiatric co-treatment.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…A total of 20% of respondents were African American, 73% were unemployed or disabled, and 54% were married. In comparison, 37% of the PPP population are African American, 60% are unemployed or disabled, and 36% are married [35]. While approximately 25% of the clinic's total population had seen the clinic psychiatrist, most respondents in this study (54%) received psychiatric co-treatment.…”
Section: Resultsmentioning
confidence: 72%
“…The study was conducted at the PPP, a multidisciplinary transitional perioperative pain service at The Johns Hopkins Hospital in Baltimore, Maryland. A summary of the clinical workflow and outcomes of the PPP has been described previously [34,35]. Briefly, patients eligible for the PPP are surgical candidates on preoperative opioids, opioid-naïve participants at risk of chronic opioid therapy after surgery (e.g., surgery severity, high-dose MME at discharge, psychiatric comorbidities), or patients with a current or past history of OUD.…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Engaging surgical patients in perioperative pain management is essential to optimize recovery, and patients are encouraged to work with their clinicians to identify treatment goals and successfully manage pain using current, safe, and effective treatments. We have shown that perceived engagement in pain management is significantly associated with reduction in prescription opioid use after surgery 7…”
Section: Personalized Pain Program At the Johns Hopkins Hospitalmentioning
confidence: 95%
“…We have shown that perceived engagement in pain management is significantly associated with reduction in prescription opioid use after surgery. 7 To improve patient engagement in the PPP, we applied a human factors and systems engineering approach to develop a multifaceted intervention including (1) a patient navigation tool for patients to document their pain experience and prepare for their PPP visits, (2) a PPP website with instruction videos to introduce the PPP and multimodal analgesic regimen to patients, and (3) a PPP brochure to provide current PPP information to both referring clinicians and potential patients. Both PPP patients and clinicians believed that the intervention was easy to use and has the potential to improve patient engagement by facilitating information sharing between patients and clinicians and empowering patients to work with their clinicians to set goals and develop plans for their treatment.…”
Section: Patient Engagement In Pain Managementmentioning
confidence: 99%